Theoretical exploration of thermodynamic characteristics in lead-free liquid alloys: Zn-Bi-In System - Sah, Sanjay Kumar; Jha, Indu Shekhar; Koirala, Ishwar (BIBECHANA, 2024)
The calculations of Zn activities in the ternary liquid solder alloy Zn-Bi-In at 873 K were conducted through the application of the Molecular Interaction Volume Model (MIVM). The calculated values were compared to experimental data for three different cross-sectional examinations, namely for the bismuth-to-indium ratios (xBi: xIn) of 1:2, 1:1, and 2:1. Moreover, the integral excess free energy of these ternary liquid alloys was assessed using the same model parameters in order to test their validity. Then, the values were compared to the relevant experimental data reported in the literature that was already in existence. A satisfactory concordance has been observed between the theoretical predictions and the experimental findings.